PERBEDAAN HASIL BELAJAR EKONOMI ANTARA METODE KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DENGAN METODE CERAMAH PADA SISWA KELAS X DI SMA NEGERI 3 CIBINONG - Galuh Prahasiwi Kusuma Wardyani; Ari Saptono; Rd. Tuty Sariwulan (Faculty of Economics, State University of Jakarta., 2014)
This study aims to determine whether there are differences in learning outcomes Understanding matter Economic Concepts in Relation to Demand, Supply, and Price balance between cooperative method Teams Games Tournament (TGT) with a lecture in class X in SMAN 3 Cibinong. The method used was experimental. Data processing by using a mix of research methods. Use traditional research sample purposive sampling method. Objective assessment instruments using multiple choice test of 20 items. Test requirements analysis is the normality test X1 and X2 with Liliefors test, homogeneity test with Fisher formula, hypothesis testing with test two average difference (t-test) free samples. Processing data using Microsoft Excel 2007 program. Research results obtained t greater than t table so that the null hypothesis is rejected, there is a material difference in learning outcomes Understanding Economic Concepts in Relation to Demand, Supply, and Price balance between methods Cooperative type Teams Games Tournament (TGT) with a lecture in class X in high school State 3 Cibinong. Keywords: learning outcomes, Teams Games Tournament (TGT), lectures